Financial Implementation for Start-up Business Home Care Applications - Hanifatul Riskiya; Tantri Yanuar Rahmat Syah; Samerdanta Pusaka; Dadan Ramdhani (Penerbit Kemala Indonesia, 2020)
In the business competition in healthcare start-up industry that is getting tougher and very fast, companies need to make and plan a financial strategy, especially an investment strategy. This is to deal with funding needs and financial needs in order to compete in the start-up ecosystem, in this case the health start-up. To capture this financial strategy, companies must have added value in financial investment planning PT. Rembaka Catur Sekawan as a company that has 4 Care brand products. Here, must have a good financial strategy to be able to compete with competitors in the market. To survive this company's must be focused on activities and business processes with concentrate on product development and financial efficiency in order to maintain the sustainability of the company. Therefore, our initial business focused on how to calculate the investment value by calculating the IRR, NPV and payback period of this business plan. To determine the feasibility of this business, it is necessary to have a Financial Strategy of proper and qualified investment feasibility and always keep up with the times.